2018
DOI: 10.1186/s40779-018-0186-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the prevalence and co-morbidities of obstructive sleep apnea in active-duty army personnel in the three southernmost provinces of Thailand using questionnaire screening

Abstract: BackgroundIt is crucial for the army to know the prevalence of obstructive sleep apnea (OSA) syndrome in active-duty army personnel. Little information has been reported on the prevalence of OSA and clinical features in active-duty army personnel. This study was aimed to estimate the prevalence of snoring and risk of developing OSA in active-duty army personnel in Thailand and to identify the co-morbidities of OSA. In total, 1107 participants who were aged 20–60 years and were deployed to the three southernmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…OSA prevalence studies worldwide showed a wide variability in the type of outcome and instrument used. Studies also utilised screening questionnaires followed by sleep studies 52,113,114 . Questionnaire based studies in Thailand reported 58.5% snoring and 4.8% prevalence of snoring and OSA respectively 114 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OSA prevalence studies worldwide showed a wide variability in the type of outcome and instrument used. Studies also utilised screening questionnaires followed by sleep studies 52,113,114 . Questionnaire based studies in Thailand reported 58.5% snoring and 4.8% prevalence of snoring and OSA respectively 114 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies also utilised screening questionnaires followed by sleep studies 52,113,114 . Questionnaire based studies in Thailand reported 58.5% snoring and 4.8% prevalence of snoring and OSA respectively 114 . In some studies, an increased association with BMI and Adjusted neck circumference was found.…”
Section: Discussionmentioning
confidence: 99%